Peranan Intelijen Kejaksaan dalam Pengungkapan Kasus Tindak Pidana Korupsi - I Made Dwi Narendra Dananjaya; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2022)
Corruption is a crime that is very detrimental to the community's economy which causes social inequality as a result of the corruption. Therefore, the role of the prosecutor's intelligence in disclosing corruption cases is very necessary to eradicate corruption in Indonesia. This study aims to examine the role of Buleleng State Prosecutor's Intelligence in disclosing corruption cases and uncover the obstacles faced by Buleleng State Prosecutor's Intelligence in disclosing corruption cases. The type of research used is empirical legal research with a statutory approach, carried out by analyzing an applicable regulation whether it is effective in the field. Sources of data used are primary and secondary data, and data collected by interview and observation techniques. Furthermore, it is processed qualitatively descriptively. The results of the study indicate that the role of the prosecutor's intelligence in corruption cases has several obstacles in its performance to eliminate corruption in Indonesia due to several factors that occur in the field of course this is detrimental to the community and also related agencies.